Scene Reconstruction in the Docudrama Film "Remedi" as an Advocacy Strategy on Sexual Violence Against Persons with Disabilities (Cinematology: Journal Anthology of Film and Television Studies, 2025)
The docudrama film Remedi was created as an advocacy medium to voice the issue of sexual violence against persons with disabilities, a topic that remains underrepresented in Indonesian cinema. This study employs a qualitative method with a phenomenological approach to explore the subjective experiences of survivors, along with a scene reconstruction strategy as a form of sensitive and ethical visual representation. The findings indicate that the integration of survivors’ daily-life documentation with fictional reconstruction is able to create a balance between factual accuracy and emotional depth, thus providing space for victims to express their voices without having to relive their trauma. These findings affirm that docudrama functions not only as a medium of representation but also as an effective instrument of social advocacy in building public awareness, fostering empathy, and encouraging the emergence of policy support that is more inclusive toward vulnerable groups. Accordingly, Remedi demonstrates how cinema can serve as both a creative medium and a tool for social change that stands in solidarity with persons with disabilities who are victims of sexual violence.